Clinical course of 63 patients with neonatal onset urea cycle disorders in the years 2001-2013 - Unsinn, Caroline; Hoffmann, Georg F. (Orphanet journal of rare diseases, 2016)
Urea cycle disorders (UCDs) are rare inherited metabolic defects of ammonia detoxification. In about half of patients presenting with a UCD, the first symptoms appear within a few days after birth. These neonatal onset patients generally have a severe defect of urea cycle function and their survival and outcome prognoses are often limited.